2016
DOI: 10.5194/se-7-599-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wood chip amendments on the revegetation performance of plant species on eroded marly terrains in a Mediterranean mountainous climate (Southern Alps, France)

Abstract: Abstract. The establishment of plant species can limit soil erosion dynamics in degraded lands. In marly areas in the Southern French Alps, both harsh water erosion and drought conditions in summer due to the Mediterranean mountainous climate prevent the natural implementation and regeneration of vegetation. Soil fertility improvement is sometimes necessary. With the purpose of revegetating such areas, we aimed to evaluate the effects of wood chip amendments on the revegetation performance of different native … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 45 publications
(48 reference statements)
3
16
1
4
Order By: Relevance
“…1). Similar results were reported by Breton et al (2016) in a study of soil amended with wood chips, where survival rates increased by 30 %. The results are also consistent with those of Querejeta et al (2001) and Castillo et al (2001), who reported that revegetation programs in semiarid conditions needed previous soil preparation for increasing water availability for plants.…”
Section: Available Water For Plants and Their Impact On Vegetation Essupporting
confidence: 78%
See 2 more Smart Citations
“…1). Similar results were reported by Breton et al (2016) in a study of soil amended with wood chips, where survival rates increased by 30 %. The results are also consistent with those of Querejeta et al (2001) and Castillo et al (2001), who reported that revegetation programs in semiarid conditions needed previous soil preparation for increasing water availability for plants.…”
Section: Available Water For Plants and Their Impact On Vegetation Essupporting
confidence: 78%
“…According to Haase and Rose (1993) soil preparation in these regions could be a powerful tool for reducing the possible plant stress suffered during the lack of water in summer. Several studies have demonstrated that the supply of organic materials could enhance the establishment of young plants and, in some cases, reduce the mortality rates in the initial stages (Woods et al, 2012; Be- Hosseini Bai et al, 2014;Breton et al, 2016). Our results showed a significant effect of the type of plant species (Table 1a; P = 0.008) and soil amendment (Table 1a; P = 0.000) on plant survival rates.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…En las áreas semiáridas Mediterráneas, las actividades antrópicas (arado en pendientes, deforestación y sobrepastoreo) y la alternancia climática de largos periodos de sequía, que se intercalan con periodos cortos de precipitación intensa, han conllevado una intensa degradación de los suelos generando una pérdida de diversidad sistémica (Casals et al, 2000;Muñoz-Rojas et al, 2016;Martínez-Murillo et al, 2017a, 2017b. Concretamente, en los suelos forestales, esto es porque la dinámica del carbono orgánico del suelo (SOC) suele estar condicionada por aquellos factores relativos a la temperatura y humedad del suelo (Ruiz-Sinoga et al, 2009;Hueso-González et al, 2014;Bretón et al, 2016).…”
Section: Introductionunclassified
“…Sin embargo, después de una repoblación, durante los primeros estadios de la vegetación, siembra y establecimiento del plantón, los beneficios de la vegetación sobre el suelo aún no se hacen manifiestos y los suelos siguen siendo altamente vulnerables a la erosión y pérdida de carbono orgánico (Maestre et al, 2003;HuesoGonzález et al, 2016). En estos primeros años, se ha demostrado que los procesos de degradación podrían minimizarse mediante la implementación de técnicas encaminadas a la protección del suelo como son el uso de residuos orgánicos tanto animales como vegetales (Jordán et al, 2010;Bretón et al, 2016;Pal y Mahajan et al, 2017;Wahbi et al, 2017). En este sentido, el efecto de varias enmiendas orgánicas, incluidas lodos de depuradora, estiércol o acolchados orgánicos ha sido objeto de numerosos estudios (Guerrero et al, 2001;Ojeda et al, 2003;Jordán et al, 2011;Jiménez et al, 2013;Tejada y González, 2013;Iglesias et al, 2015;Dudás et al, 2016;Prosdocimi et al, 2016).…”
Section: Introductionunclassified